Cognitive Behavioural Therapy as a Counselling Strategy for Handling Gambling Behaviour among Undergraduates in Nigeria (Journal of Guidance and Counselling Studies, 2025)
Gambling behavior among undergraduates in Nigeria has become an increasing concern for  stakeholders, particularly school counsellors. This issue poses significant challenges to students’ academic performance, mental health, and overall well-being. Therefore, effective interventions are needed to address gambling addiction within this population. This paper aims to examine the relevance of Cognitive Behavioural Therapy (CBT) as a counselling intervention for managing gambling behaviour among undergraduates. It presents a comprehensive review of the concept of gambling behaviour, explored the factors contributing to gambling addiction, and discussed the core components of CBT tailored to address gambling problems. Additionally, the therapeutic process of CBT and its proven effectiveness in treating gambling addiction are analyzed. Based on the review, it was suggested that counsellors support students in identifying and challenging cognitive distortions linked to gambling. Counsellors should also equip students with alternative coping strategies to replace gambling behaviours and promote healthier emotional regulation. By integrating CBT into counselling services, school counsellors can play a pivotal role in helping students overcome gambling addiction and enhance their overall well-being.